1996
DOI: 10.1161/01.str.27.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Stroke and Obstructive Sleep Apnea

Abstract: Patients with stroke have an increased incidence of obstructive sleep apnea compared with normal sex- and age-matched control subjects. Hypoxia and hemodynamic responses to obstructive sleep apnea may have predisposed these patients to stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
244
1
19

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 482 publications
(271 citation statements)
references
References 21 publications
7
244
1
19
Order By: Relevance
“…[5] It is likely that the same mechanisms are valid in humans too, since obstructive sleep apnea leads to increased SNS activity and increased daytime blood pressure. [6][7][8] Obstructive breathing disorders are associated with cardiovascular diseases such as hypertension, [9][10][11] myocardial infarction, [12] stroke, [13] and heart failure. [14] When treated with continuous positive airway pressure (CPAP) during sleep, daytime blood pressure and sympathetic activity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…[5] It is likely that the same mechanisms are valid in humans too, since obstructive sleep apnea leads to increased SNS activity and increased daytime blood pressure. [6][7][8] Obstructive breathing disorders are associated with cardiovascular diseases such as hypertension, [9][10][11] myocardial infarction, [12] stroke, [13] and heart failure. [14] When treated with continuous positive airway pressure (CPAP) during sleep, daytime blood pressure and sympathetic activity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…It also revealed that it is unclear to what extent the sleep problems reported in the early phase after a stroke are transient. Some authors suggest that post-stroke sleep disturbances actually persist and become a chronic condition [10][11][12][13], but the evidence-base for this claim is poor and the prognosis beyond one-year post injury is not well understood. This is partly due to the use of heterogeneous study groups comprised of patients in various stages of recovery and with various levels of functional ability.…”
Section: Introductionmentioning
confidence: 99%
“…OSA is characterized by repetitive collapse of the pharyngeal airway during sleep, yielding hypoxia, hypercapnia, and arousal from sleep to reestablish airway patency [2]. The associated consequences include daytime sleepiness [3], decreased cognitive performance, decreased quality of life [4], increased risk of automobile and industrial accidents [5,6], and adverse cardiovascular sequelae [7][8][9][10]. Treatment of OSA leads to improvements in many of these adverse outcomes and may reduce healthcare costs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%